Platon Ivanovich Tikhov, Professor of Surgery of the Imperial Tomsk University (to 145th anniversary) - G. V. Fyodorova; D. V. Scherbakov (Бюллетень сибирской медицины)
The number of publications devoted to the development of medicine in Siberia is increasing in the last years, but still insufficient. In this paper, the authors tried to reconstruct the biography of Platon Ivanovich Tikhov, Professor of the Tomsk Imperial University, whose results enriched the Russian and international surgical science in the field of osteoplastic operations, surgery of abdominal cavity and parenchymal organs, blood vessels and heart, anaesthetization. P.I. Tikhov was the first in Siberia, who performed the heart wound closure operation (1907).